ÎNFIINȚAREA ȘI ACTIVITATEA TRIBUNALELOR REGIONALE ȘI A CELOR ȚINUTALE DIN BASARABIA (1812 - 1828) - Artur LEȘCU (Buletinul Științific al Universității de Stat „B.P. Hasdeu” din Cahul: Științe Sociale, 2019)
The present article analyzes the problems related to the establishment and activity of regional and county courts in Bessarabia during the years 1812 - 1828. Immediately after the annexation, the Russian government began to implement the law system, specific to this country. Initially, Russian law introduced criminal law and law on police bodies in Bessarabia. Increased attention was paid to maintaining the order of law and legislation, by establishing the judicial system. The supreme judicial institutions in Bessarabia were the Regional Criminal Court and the Regional Civil Court. Civil law was based on Moldovan rights and customs, and the criminal law - on Russian law. The lower court was represented by the county courts, which were responsible for solving all crimes and disputes, civil and criminal. Based on the unpublished documents, the author demonstrates the process of setting up and working the regional and county courts in Bessarabia.